PORTFOLIO OPTIMIZATION WITH LINEAR PROGRAMMING BASED ON TRAPEZOIDAL FUZZY NUMBERS - Serkan Akbaş; Türkan Erbay Dalkılıç (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In today's developing financial markets, variouscomplex techniques are used in the creation of portfolios that will provide thebest return to the investors. In this study, a portfolio selection model thatincludes investment data and expert opinions is proposed. This model consistsof two stages. In the first stage, the weight of the criteria in the portfolioselection problem was determined by the Constrained Fuzzy Analytic HierarchyProcess method proposed by Enea and Piazza. In the second stage, the modelproposed by Lai and Hwang was used to solve the problem of fuzzy linearprogramming to be formed by using the determined criteria weights. These twomethods in the literature use triangular fuzzy numbers to solve the problem.The methods used in this study were developed for trapezoidal fuzzy numbers(TrFNs) and an alternative method for portfolio selection problems wasproposed.